MENILAI KEBERHASILAN SISTEM KEUANGAN DESA (SISKEUDES): VALIDASI MODEL KEBERHASILAN SISTEM INFORMASI DELONE DAN MCLEAN - Sigit Kurnianto; Deddy Kurniawansyah; Wulandari Fitri Ekasari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2019)
This study aims to test the success Siskeudes by developing a successful model of the DeLone and McLean information systems into seven dimensions. The population was 151 siskeudes operatos in the village goverments Gresik, Nganjuk, Situbondo. The sampling used in this study a sensus method. Source of data is primer data, obtained questioner from respondend. This study used structural equation modeling (SEM). The results obtained in this study is system quality has a effect on system satisfaction, information quality has a effect on information satisfaction, usefulness has a effect on system satisfaction and information satisfaction, system satisfaction has effect on individual impacts, information satisfaction has a effect on conflict intentions, individual impacts has a effect on organizational impacts, except information qualityto usefulness, system quality to information satisfaction, usefulness to individual impacts, usefulness to organizational impact, system satisfaction to organizational impact, information satisfaction to organizational impact. In addition, the test results show that there are nine pathways that have additional influence through indirect pathways. This finding becomes the basis for the development of a successful model of information systems in eGovernment, for regulators to develop and manage strategies for implementing the Siskeudes application, and as a guide for evaluating the success of Siskeudes.